2021
DOI: 10.2478/sjce-2021-0001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Temperature on the Modal Properties of a Steel Railroad Bridge

Abstract: The article is devoted to a study of the impact of various environmental conditions on modal parameters, such as natural frequencies and damping ratios. The modal analysis has been performed using the Stochastic Subspace Identification (SSI) method of measuring data every month on the same steel bridge structures located on an important railroad route from Prague (the Czech Republic) to Košice (Slovakia). The structure is approximately 60 m long, and the bearing structure is formed by two arch trusses. The bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…A similar phenomenon was observed at the Saint Michel Bridge [17]. Michal and Katarína [18] used the Random Subspace Method to identify acceleration data from a steel bridge and processed it in conjunction with temperature data. They observed that the first two frequency modes of the structure increased with rising temperature, and some frequencies showed non-linearity when fitted with linear regression functions against temperature data.…”
Section: Introductionsupporting
confidence: 53%
“…A similar phenomenon was observed at the Saint Michel Bridge [17]. Michal and Katarína [18] used the Random Subspace Method to identify acceleration data from a steel bridge and processed it in conjunction with temperature data. They observed that the first two frequency modes of the structure increased with rising temperature, and some frequencies showed non-linearity when fitted with linear regression functions against temperature data.…”
Section: Introductionsupporting
confidence: 53%
“…Moreover, other studies employed qualitative and quantitative methods based on surveys, interviews, and focus groups to identify the influence factors ( 4345 ). Young et al ( 46 ) and Rudin-Brown et al ( 47 ) examined where drivers direct their attention while approaching the intersection and whether this differs between novice and experienced drivers. These studies, using a driving simulator, also compared the efficacy and drivers’ subjective perception of level crossing traffic control devices such as flashing lights with boom barriers and standard traffic lights.…”
Section: Related Workmentioning
confidence: 99%
“…In the same vein, Venglar ( 46 ) proposed an “Improved Transition Preparation Strategy” (ITPS) to enhance mobility and safety near crossings. This investigation added more logic tests to the ITPS algorithm, aiming to provide more green time for the conflicting phases with a train crossing.…”
Section: Related Workmentioning
confidence: 99%
“…Since the bridge structure is always subjected to complex environmental effects, it is essential to assess the impact of environmental thermal effects on the structure itself (Nandan and Singh, 2014). However, medium and small span bridges on highways are mainly subjected to two types of variable loads, vehicle live action and temperature action (Venglár and Lamperová, 2021). And the temperature action is directly affected by climatic conditions (Shan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%